Os sentidos da cirurgia estética: utilidade, futilidade, agência e/ou incorporação - Castro, Ana Lúcia de [UNESP] (My University, 2012)
This article aims to reflect on the growth of the practice of plastic surgery for cosmetic purposes and its relationship with the contemporary consumer culture. In other words, we discuss how this practice expresses the values and principles for consumer culture and configures itself differently in different contextsin, as the cities of Sao Paulo and London, where he held field work involving the collection of information in press materials, data files, interviews and observation in clinical aes‐ thetic.

Este artigo busca contribuir para a reflexão acerca do crescimento da prática da cirurgia plástica pa‐ ra fins estéticos e sua relação com a cultura de consumo contemporânea. Em outras palavras, dis‐ cute‐se a maneira como esta prática expressa valores e princípios estruturadores da cultura de con‐ sumo e ganha contornos diferenciados em contextos particulares, como as cidades de São Paulo e Londres, onde realizou‐se trabalho de campo, envolvendo a coleta de informações em material de imprensa, dados em arquivos, entrevistas e observação em clínicas estéticas.
The senses of cosmetic surgery: utility, futility, the agency and/or the incorporation
Keywords: Cosmetic surgery; Body cult; Consumer culture; Agency; Cirurgia plástica; Culto ao corpo; Cultura de consumo; Agência